Managerial and Economic Aspects of the International Mergers and Acquisitions in Bulgaria - Tzanov, Tzvetomir (Research Papers, 2006)
The current paper focuses on merger and acquisition (M&A) transactions led by foreign investors in Bulgaria in the years of transition and economic restructuring as well as ongoing integration into the EU. The research emphasizes on major managerial aspects of the transactions (such as strategic planning, relatedness, problems of integration) as well as selected economic issues (modes of restructuring, possible effects, etc.).The analytical framework of research has been provided through an interdisciplinary approach to M&As (theory of mergers hypotheses combined with an international business perspective).Empirical data has been gathered through qualitative methods of research, such as unstructured and semi-structured interviews, structured inquiry through questionnaires distributed among foreign investors in Bulgaria, case studies. Quantitative methods (T-test, Mann-Whitney test, and correlation analysis) through SPSS 11.5 statistical package were also applied in deriving results and conclusions.Some of the major conclusions relate to motives for investment through M&As, strategic planning of the transactions, relatedness, inter and intra-firm integration, accommodation of the foreign investor in a cross-cultural context, contribution to the local subsidiary, evaluation of the transaction success, possible tendencies for future development, etc.